2019
DOI: 10.1111/mec.15253
|View full text |Cite
|
Sign up to set email alerts
|

Stacks 2: Analytical methods for paired‐end sequencing improve RADseq‐based population genomics

Abstract: For half a century population genetics studies have put type II restriction endonucleases to work. Now, coupled with massively‐parallel, short‐read sequencing, the family of RAD protocols that wields these enzymes has generated vast genetic knowledge from the natural world. Here, we describe the first software natively capable of using paired‐end sequencing to derive short contigs from de novo RAD data. Stacks version 2 employs a de Bruijn graph assembler to build and connect contigs from forward and reverse r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
689
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 790 publications
(758 citation statements)
references
References 79 publications
3
689
0
2
Order By: Relevance
“…Loci were identified and genotyped in STACKS v.2.2 (Rochette et al, 2019) without using gapped alignments. Raw reads were demultiplexed and barcodes were trimmed in process_radtags (parameter flags: -e SbfI , -c, -q, -filter_illumina, -r, --bestrad).…”
Section: Methodsmentioning
confidence: 99%
“…Loci were identified and genotyped in STACKS v.2.2 (Rochette et al, 2019) without using gapped alignments. Raw reads were demultiplexed and barcodes were trimmed in process_radtags (parameter flags: -e SbfI , -c, -q, -filter_illumina, -r, --bestrad).…”
Section: Methodsmentioning
confidence: 99%
“…We included four assemblers that use graph‐based algorithms in our comparison: Stacks (version 1.46), Stacks2 (version 2.1), ABySS (version 1.3.4) and Velvet (version 1.1) (Catchen et al, ; Rochette et al, ; Simpson et al, ; Zerbino & Birney, ). We evaluated both Stacks and Stacks2 due to significant changes in the software related to how insertion and deletion (indel) variation is treated (changes to Stacks2 since the version 2.1 we used have not included changes to de novo assembly).…”
Section: Methodsmentioning
confidence: 99%
“…We report the software that was used in those studies and the extent to which papers evaluated and reported different assemblies based on different software settings and parameters. Some software was designed specifically for assembling RAD sequences (e.g., Stacks ; Catchen, Amores, Hohenlohe, Cresko, & Postlethwait, ; Rochette, Rivera‐Colon, & Catchen, ). Other programs were designed for assembly of whole genomes, transcriptomes, or protein sequences, including assembling contiguous sequences (contigs) that are longer than raw reads from the sequencing instrument (e.g., Velvet ; Zerbino & Birney, ).…”
Section: Introductionmentioning
confidence: 99%
“…Raw reads obtained through an Ion S5 sequencer (Thermo Fisher Scientific Inc., Waltham, MA, USA) were trimmed according to the enzyme recognition sequence, and after a quality check, all the artifacts and the Ns-containing reads were removed. Variants were called using the Stacks v2.41 software [25], and SNPs were filtered to remove those meeting the following criteria: (1) SNPs with more than 10% missing data, (2) SNPs with a sequence depth ≤ 4, and (3) tri-and tetra-allelic SNPs.…”
Section: Snp-based Genotyping By Rad-seq Analysismentioning
confidence: 99%